Synthesis of new azo dyes of uracil via ecofriendly method and evaluation for the breast, liver and lung cancer cells in vitro - Saripah Salbiah Syed Abdul Azziz (Tanjung Malim, 2023)
Synthesis of new azo dyes of uracil via ecofriendly method and evaluation for the breast, liver and lung cancer cells in vitro by Saripah Salbiah Syed Abdul Azziz